Acupuncture for Anaemia and Large Intestine Impaction Associated with Hind Limb Weakness in a Horse: A Case Report - María Resano-Zuazu (Medical Association of Pharmacopuncture Institute, 2020)
A 24-year-old horse was presented with a clinical history of anaemia, large intestine impaction and hind limb weakness. Loss of body weight was also reported. Hematocrit and hemoglobin levels were low and piroplasmosis test was negative. Nasogastric intubation with laxative agents was performed and 50 ml of a red blood-cell-supplement was given daily during a month. An assessment following Traditional Chinese Veterinary Medicine (TCVM) principles was performed after the last episode of large intestine impaction. A swollen, pale and wet tongue was observed. A superficial, weak pulse combined punctually with a slippery pulse was detected on the right side. The pulse on the left side was very thin. BL18, BL20 and BL23 were the most sensitive acupoints on the right side. BL18 and BL23 were the most sensitive on the left. TCVM diagnosis was Qi/Yang Kidney Deficiency, Spleen Qi Deficiency with Stagnation and Blood Deficiency. It received acupuncture at Bai-Hui, KI3, KI7, KI10, BL23, GB39, ST36, BL17 and acupressure at SP10. The client reported a significant improvement after treatment and hematocrit and hemoglobin levels were normal. KI3, ST36, BL39 acupoints were treated 14 days later. The outcome was favourable and one acupuncture session per month was recommended. No previous case reports in equines have been documented with a combination of blood, gastrointestinal and musculoskeletal problems in the same episode. This case is an example of an integrative approach to investigate the origin and the interdependent relation between body systems.